Crust or core? Insights from the slow rise of large glitches in the Crab pulsar. (20th September 2018) - Haskell, B; Khomenko, V; Antonelli, M; Antonopoulou, D
ABSTRACT: Pulsar glitches are attributed to the sudden recoupling of weakly coupled superfluid components in the neutron star interior. The transfer of angular momentum between the components is regulated by mutual friction, whose strength defines the spin-up time-scale of a glitch. Hence, observations of glitch rises can be used to shed light on the dominant microphysical interactions at work in the interior of the star. We present a model which naturally produces a fast spin-up followed by a more gradual rise, as observed in large glitches of the Crab pulsar, including the largest recent glitch of 2017. Our model is then used to determine whether the glitch driving region is located in the crust or core of the star. To do this, we compare our results to observations of large glitches in the Crab and Vela pulsars and obtain constraints on the mutual friction parameters that govern the coupling between the superfluid and the crust. Our results are consistent with theoretical estimates for mutual friction in the core for the Vela, but with estimates for the crust in the Crab. This suggests a crustal origin for Crab glitches, but an outer core contribution for Vela glitches.